Acceptability and Use of a Jelly Prepared from Acerola Fruit Pulp and Juice - K. Caetano, Priscilla; R. Daiuto, Erica; L. Vieites, Rogerio; E. Smith, Robert (Natural Products Journal, The, 2014)
The objective of this work was to evaluate the acceptability and shelf life of an acerola (Malpigia emarginata DC) jelly prepared in different ways. The jellies were prepared using sugar and either acerola juice or pulp and 1% pectin in aluminum, copper and stainless steel pans. They were submitted for sensorial and physical-chemical analyses to determine the most acceptable product and to establish its shelf life. To determine the shelf life, physical-chemical, nutritional, microbiological and sensorial properties were evaluated, along with color. The most acceptable high-quality jelly was prepared with equal amounts of pulp and sugar, in an aluminum pan. It had good acceptability, so it can be commercialized and stored for 180 days.
Keywords: processing